Molecular and behavioural characterisation of novel alpha-synuclein BAC transgenic mouse models of Parkinson's disease - Janezic, S (2013)
Alterations in the expression levels of α-synuclein (SNCA) provide an important link between familial and sporadic forms of Parkinson’s disease (PD). Multiplications of the human wild-type SNCA locus give rise to early-onset autosomal-dominant forms of PD and elevated α-synuclein expression has been linked to an increased risk for late-onset sporadic PD. The identification of α-synuclein’s physiological and pathophysiological functions has been hindered by a lack of animal models that accurately recapitulate the key disease features. Traditional cDNA-based transgenic models fail to correctly reflect the spatiotemporal expression pattern of α-synuclein and consequently do not accurately model the disease. Bacterial artificial chromosome (BAC) technology allows transgene expression from the entire genomic locus under the control of native regulatory elements and therefore allows improved modelling of disease mechanisms and phenotypes. This thesis describes a longitudinal characterisation of the molecular and behavioural effects of overexpressing human wild-type α-synuclein in a novel BAC transgenic PD mouse model, the SNCA-OVX model. Firstly, the work investigates transgene expression and localisation, dopamine neuron loss, synaptic function and PD-related motor and non-motor phenotypes. At 3 months of age, deficits in gastrointestinal function were observed while normal levels of dopaminergic markers and neurons were maintained. At 18 months, mice displayed a 30% decrease in nigrostriatal dopamine neurons, accompanied by reduced motor coordination and function. This novel PD model, which reflects accurate transgene expression and displays progressive dopamine neuron loss accompanied by characteristic behavioural PD phenotypes, will aid the investigation of molecular disease mechanisms and the development of novel therapies. Secondly, this thesis describes the generation of Translating Ribosome Affinity Purification (TRAP) transgenic mice, which express an EGFP-tagged ribosomal protein L10a transgene under the control of the tyrosine hydroxylase promoter. Finally, double transgenic TH bacTRAP SNCA-OVX mice were generated to investigate changes in genome-wide gene expression in dopaminergic cell populations of SNCA-OVX mice to identify novel drug targets.